Juridical Overview of the Syndication Financing Agreement Between Customers and Financial Institutions - Suwinto Johan; Ariawan Ariawan (Kanun Jurnal Ilmu Hukum, 2021)
Companies need funding for business growth. Syndicated financing is financing in large amounts of funds and projects that require extensive and long-term financing. Syndi-cated financing has grown since the 1960s. Participating financial institutions have compliance and knowledge of syndicated financing agreements. Customers have low compliance and understanding of financing agreements. This discrepancy has given rise to several communication problems, which resulted in legal events. This research aims to examine syndicated financing agreements between financial institutions and customers from the juridical side. This research uses a normative juridical method. This research concludes that the financing agreement is a single agreement between customers and many financial institutions. Financial institutions cannot deal directly with customers in the syndicated financing agreements. The facility agent or trustee represents the financial institution in negotiations with the customer if there is a difference or discrepancy with the financing agreement.